Peningkatan Motivasi Belajar Siswa pada Materi Reaksi Reduksi Oksidasi melalui Model Pembelajaran Flipped Classroom dengan Cooperative Learning - Dian Lestari; Nurbaity Nurbaity; Tritiyatma Hadinugrahaningsih (LPPM Universitas Negeri Jakarta, 2017)
This study aims to improve student’s learning motivation on oxidation-reduction reaction material through flipped classroom learning model with cooperative learning. Cooperative learning which applied in this research is Number Head Together (NHT) type. The study was conducted in the 2nd term of academic year 2016/2017 at one of public senior high school in Jakarta. The research method which had been used is Classroom Action Research through four stages, planning, implementation, observation and reflection phase. This research was conducted in two cycles until all six indicators of student learning motivation are achieved. The indicators that used to determine student’s learning motivation include student’s interest in learning process, student’s attention in the learning process, the responses are shown to the stimulus given by the teacher, the spirit of the student’s to do the tasks, the responsibility at finished the work, happiness, and satisfaction of student’s in doing the task given by the teacher. The first cycle produces two indicators, student’s interest in the learning process and responsibility at finished the task. In the second cycle, all indicators have been reached. Along with the increase of student’s motivation, the average of student’s learning also increases. Flipped classroom learning with cooperative learning could make a positive impact for improvement of student learning motivation. Keywords: Student Learning Motivation, Flipped classroom, Number Head Together